Indicadores fisiológicos, bioquímicos e moleculares em cártamo (Carthamus tinctorius L.) submetido ao estresse salino e déficit hídrico - Bezerra, Lisiane Lucena (Brasil, 2015)
Carthamus tinctorius L. is promising specie for biodiesel production due to its better adaptation to low rainfall regions, moderate tolerance to salinity and good capacity to grow in different arid and semi-arid regions in the world. Meanwhile, its physiological, biochemical and molecular mechanisms involved in tolerance or susceptibility to salt and drought stresses are not yet fully understood. The aim of this work was to analyze growth and water status indicators as well as the possible contribution of inorganic and organic solutes in osmotic adjustment. Also, we have carried out semi-quantitative RT-PCR assays to detect P5CS, P5CR and BADH, enzymes involved in proline and glycine betaine pathways respectively in leaves and roots submitted to salt stress and drought. C. tinctorius responds differently to salt (50-100 mM NaCl) and water (-0.25 to -0.50 MPa PEG 6000) stresses. Treatments with NaCl and PEG 6000 have induced significant changes in growth, organic and inorganic solutes content and gene expression. However the intensity and type of response were different for each stress condition. Safflower was more sensitive to water stress. Salt stress has increased Na+ content in the leaves (8x in plants exposed to 100 mM NaCl and 2x in roots treated with NaCl 50 mM). Drought caused K+ accumulation in the leaves (Na+/K+ higher than 0.6) indicating a possible ionic toxicity. Organic solutes (sugar, protein, amino acid, proline and glycine betaine) have accumulated in leaves when submitted to water deficit as also in roots (proteins, amino acids and glycine betaine consider levels, and the roots accumulated proteins, amino acids and glycine betaine). Such effects show a possible osmotic adjustment. When treated with NaCl, the plants kept the content of organic solutes in the control. The gene marker expression shown that P5CS gene was expressed only in safflower leaves under salt and water severe stresses (100 mM NaCl and -0.50 MPa). P5CR was detected in all treatments and in the same level as well as in leaves and roots. BADH has been expressed in leaves only when subjected to drought. In roots, there was expression in both stresses (salt and water deficit). Safflower plants respond differently to the effects of salinity and water stress showing that plant response is treatment, dose and organ dependent
Physiological, biochemical and molecular indicators in safflower (Carthamus tinctorius L.) submitted to salt stress and drought
Keywords: Crescimento; Ajustamento osmótico; expressão gênica; Growth; Osmotic adjustment; Gene expression; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA